Nanoencapsulation of binary nitrate molten salts for thermal energy storage: Synthesis, thermal performance, and thermal reliability - Lee, Jaejun; Jo, Byeongnam (Solar Energy Materials and Solar Cells, 2021)
Molten salts have favorable features to serve as thermal energy storage (TES) media, and their nano-sized capsules are advantageous for efficient TES. However, their high water solubility hinders encapsulation by conventional methods, such as the sol–gel process. In this study, a binary nitrate molten salt mixture (NaNO3 and KNO3 in 60:40 mass ratio) was nanoencapsulated by a silica (SiO2) shell using emulsification and sol–gel techniques. The diameters of the molten salt capsules were controlled from a few micrometers to several hundred nanometers by regulating the stirring intensity and surfactant dosage during the synthesis process. Based on differential scanning calorimetry measurements, the encapsulation ratio and encapsulation efficiency were calculated 50.6% and 50.0%, respectively. Thermogravimetric analysis confirmed that the thermally stable SiO2 shell enhances the decomposition temperature of the binary nitrate salt mixture. Finally, the proposed nanoencapsulation protocol was also utilized to encapsulate a different nitrate salt mixture (NaNO3 and KNO3 in 80:20 mass ratio) and two single nitrate salts (NaNO3 and KNO3). This was done to validate both its applicability to all nitrate salt mixtures and the consistency of the chemical composition in each nanocapsule. The achievement for these nitrates suggests the possibility of comprehensive nanoencapsulation of water-soluble materials.
Keywords: Emulsion; Mass ratio; Molten salt; Nano-encapsulation; Nitrate salts; Salt mixtures; SiO$-2$; Sol'gel; Thermal energy storage; Thermal Performance; Emulsion; Molten salt; Nanoencapsulation; Sol–gel; Thermal energy storage